RF Analysis of a Sub-GHz InP-Based 1550 nm Monolithic Mode-Locked Laser Chip - Alloush, M. Ali; van Delden, Marcel; Bassal, Amer; Kleemann, Navina; Brenner, Carsten; Lo, Mu-Chieh; Augustin, Luc; Guzman, Robinson; Musch, Thomas; Carpintero, Guillermo; Hofmann, Martin R. (IEEE photonics technology letters, 2021)
We report a monolithic sub-GHz repetition rate mode-locked laser with record low pulse-to-pulse RMS timing jitter of 3.65 ps in the passive mode locking regime. We analyse the optical pulse generation in passive and hybrid mode-locking operating regimes, finding narrower RF tone linewidth in the passive regime, attributed to the improved contact structure of the gain sections. The noise performance is also characterized in passive and hybrid regimes, showing RMS integrated timing jitter of approximately 600 fs. For hybrid modelocking, the repetition rate can be varied over a large range from 880 to 990 MHz. We observe broad pulse widths of few hundred picoseconds attributed to the (long folded) waveguide architecture and on-chip multimode interference mirrors. This device subjects a stand-alone, ultra-compact, mode-locking based clock source to realize frequency synthesizers operating over a frequency range from sub-GHz up to approximately 15 GHz.